Competence and Discipline in Improving Police Performance: Qualitative Analysis - Sari, Ayu Permata (PPSDP International Journal of Education, 2025)
This study aims to examine the extent to which the competence and work discipline of police members in the Directorate of Vital Object Security of the South Sumatra Regional Police affect their performance in carrying out security duties in the Obvitnas/Obviter area. The research method used in this study is qualitative analysis. Respondents in this study were personnel of the Ditpamobvit of the South Sumatra Regional Police who carried out security duties in the Obvitnas area: Head of Bin Opsnal, Deputy Director of Pamobvit, and Director of Pam Obvit. The location of the study was at the Ditpamobvit of the South Sumatra Regional Police. The instruments used included interviews, observations, and documentation. The steps in this study included collecting data from interviews with personnel who carried out security and the leadership of Ditpamobvit and then describing and presenting the data that had been collected in written form. The results of this study indicate that competence and work discipline greatly influence the improvement of the performance of Ditpamobvit personnel of the South Sumatra Regional Police in carrying out duties in the Obvitnas and Obviter areas.